Case series: Four fatal rabbit hemorrhagic disease virus infections in urban pet rabbits - Pinto, Filipe Fontes; Abrantes, Joana; Ferreira, Paula Gomes; Nóbrega, Mário; Marcos, Ricardo (Frontiers in Veterinary Science, 2023)
Four pet rabbits (Oryctolagus cuniculus cuniculus) were diagnosed with a fatal infection by rabbit hemorrhagic disease virus (RHDV GI.2) were identified in the same week and further investigated. All animals lived in an urban environment, were aged between 8 months and 2 years old and none were vaccinated against RHDV2 (GI.2). Three animals arrived at the clinic and died shortly afterward and it was only possible to perform their necropsy and collect material for RT-qPCR (RHDV) test. These rabbits tested positive for RHDV2, with high viral loads. In the fourth case, an additional clinical evaluation was possible. In this case, the 8 month old intact female indoor pet rabbit was presented with apathy, tachypnea and tachycardia. Radiographic projections revealed no clinical alterations. Serum biochemistry revealed a significant increase in AST and ALT with a small decrease in glucose. Abdominal ultrasound revealed an acute hepatitis. Despite hospitalization support, after 30 hours of admission, the rabbit lost consciousness and developed anorexia and pyrexia in the last minutes before death. Post-mortem analysis, including necropsy, histopathology and molecular biology, confirmed the diagnosis of RHDV2 (GI.2) infection. In conclusion, this paper reports a case series that demonstrates the severe infectious ability and the high mortality associated with RHDV even in rabbits from urban environments. Furthermore, it highlights the importance of always considering rabbit hemorrhagic disease (RHD) as a differential diagnosis in pet rabbits with nonspecific clinical signs, and should warn veterinarians that pet rabbits living indoors can also be infected with a fatal outcome.